Pengaruh Celebrity Endorser Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Skincare Scarlett Di Kota Bima - Indrawani Indrawani; Irma Mardian (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Business competition is increasingly dynamic, complex and uncertain. Not only does it provide opportunities but also challenges. This makes every company compete to achieve a competitive advantage in order to fight for market share. Every effort will continue to be made to attract potential consumers by providing information about the products they have. Companies compete with each other in marketing their products in order to position their products appropriately in the minds of consumers.